Post-crisis monetary policy frameworks in sub-Saharan Africa - Kasekende, Louis (Willey, 2011)
Most of the monetary policy frameworks which use a domestic anchor for monetary policy in sub-Saharan Africa (SSA) employ quantitative money targets. Although these frameworks proved useful in reducing inflation in SSA, they are not well suited to the discretionary fine tuning of monetary policy. Monetary policy frameworks should be reformed in the post-crisis period, especially in the ‘frontier markets’ of SSA, where the need for activist demand management will grow in line with economic development and the integration of domestic financial sectors into global markets. Reforms should include adopting a broader set of policy objectives in addition to inflation, replacing broad money as the intermediate target with a more sophisticated set of indicators and forecasts and reform of the operating target. In essence, central banks should introduce a form of inflation targeting lite. This should be complemented by measures to strengthen the transmission mechanism of monetary policy.
Keywords: Monetary Policy; Sub-Saharan Africa; Post-crisis